AML with inv(16)/t(16;16) and high-risk cytogenetic abnormalities: atypical features and unfavorable outcome. Issue 1 (31st December 2022) - Assaf, Nada; Lefebvre, Christine; Raggueneau, Victoria; Guignedoux, Geoffroy; Marceau-Renaut, Alice; Chevalier, Simon; Tondeur, Sylvie; Bories, Dominique; Benramdane, Riad; Rousselot, Philippe; Terré, Christine
ABSTRACT: Objectives: Acute myeloid leukemia (AML) with inv(16)/t(16;16) is among the most frequent AML subtypes. It is recognized by the detection of the CBFB-MYH11 fusion which confers a favorable prognosis, irrespective of the presence of secondary cytogenetic abnormalities. However, the effect of additional genetic anomalies on the behavior of inv(16) AML is debatable. Recent case reports describe an unfavorable prognosis for those patients, characterized by early relapse and death. In this study, we present a series of patients with CBFB-MYH11 fusion and high-risk rearrangements to increase knowledge about this potentially distinct subgroup. Methods: All cases with inv(16)/ t(16;16) and one or more high risk abnormalities were reviewed at two tertiary healthcare centers between years 2006 and 2020 in terms of demographics, biological and clinical data. Results: Among the total 1447 and 1283 AML cases, the frequency was found to be 0, 2% and 0.3%. Clinical data could be retrieved for 5 patients. Detected high-risk abnormalities included TP53 and 5q deletion, complex and monosomal karyotype. The median age was 67 years, with a majority of females (M:F = 1:1.5). Two out of 5 patients presented with therapy related AML, with short latency periods. All patients presented with thrombocytopenia and/or leukocytopenia. Bone marrow aspirates revealed atypical morphology and the detection of rare CBFB - MYH11 fusion transcripts. All 5 patients died, with a short mean overall survival of 5.8 months. Discussion and Conclusion: Our series suggests that the presence of high risk abnormalities confers distinct biological features and poor prognosis to inv(16) AML.